UPAYA SATUAN LALU LINTAS POLRES GRESIK UNTUK MENINGKATKAN PELAYANAN SIM DENGAN MENGGUNAKAN APLIKASI CARE (CREATIVE AUGMENTED REALITY EDUCATION) - FUTUHATUL LADUNIYAH (Advances in Police Science Research Journal, 2019)
This research is motivated by the increasing number of motorized vehicles which causes an increase in SIM manufacture at the Gresik Police Traffic Unit, causing problems, namely long service times in limited spaces and the number of officers who are not comparable to SIM applicants. So that the Care application is used to help improve SIM services. The purpose of this study is to describe the use of the Care application to improve SIM services at the Gresik Police Traffic Unit, to mention the factors that influence the use of the Care application, and to describe the efforts of the Gresik Police Traffic Unit to improve SIM services by using the Care application. This research uses a qualitative approach with field studies. The research location is at the Gresik Police Traffic Unit. Data collection methods include interviews, observations and document studies. The data validity technique uses triangulation of sources, techniques, and time. Data analysis techniques start from data collection, data reduction, data presentation and drawing conclusions. The results of the study found that in the use of the Care application there are still 2 components of the 14 service standard components, Law no. 25 of 2009, which have not met service standards, namely the legal basis and service products. The use of the Care application is influenced by supporting factors and inhibiting factors. The inhibiting factor internally is the Care application upgrade system, while externally, the user's electronic devices and public knowledge. Efforts that have been made are with 4 strategies to improve the quality of public services, namely growth strategies, increasing efficiency, stability, and collaboration. By developing SIM services with the Care application, improvements in terms of human resources, methods, and infrastructure, services based on the Gresik Police Satpas service announcement, SIM services towards digital, and cooperation with the Dikyasa unit. The suggestions are making SOP for Care applications, expanding platforms other than Android, adding Care markers, using applications in other public services, the need for forced efforts to use Care applications, guard officers at the gate portal to assist the mechanism for using applications and distributing leaflets to SIM applicants who will be using the Care application. again, increased socialization through online and print media.